Habitat use and reproductive activity of anurans from a cerrado area in Minas Gerais State, Southeastern Brazil - Fiorillo, Bruno F.; Nali, Renato C.; Prado, Cynthia P. A. [UNESP] (My University, 2019)
The Brazilian Cerrado is one of the 25 most important biodiversity hotspots, considered the most threatened savanna on earth. Amphibians are especially vulnerable to habitat modifications due to behavioural and physiological traits. Herein, we list anuran species of a Cerrado area in the municipality of Sacramento, Minas Gerais State, Brazil, after 12 months of efforts between 2010 and 2011. Also, we provide information about habitat use and reproductive activity based on field surveys, where we registered habitat occupation and temporal distribution of the anurans at the study site. A total of 20 species belonging to seven families were recorded; two species are considered Data Deficient by the IUCN Red List of Threatened Species, two have unreported status, and one is considered Critically Endangered. Moreover, seven of the 20 species need status updating. We highlight that fragments in altered areas are crucial to maintain amphibian diversity, especially for species with restricted distributions, taxonomic uncertainties and/or that require more information on their conservation status.
Keywords: Amphibians; Community; Conservation; Inventory; Neotropics